dmLT Adjuvant Enhances Cytokine Responses to T Cell Stimuli, Whole Cell Vaccine Antigens and Lipopolysaccharide in Both Adults and Infants - Akhtar, Marjahan; Nizam, Nuder Nower; Basher, Salima Raiyan; Hossain, Lazina; Akter, Sarmin; Bhuiyan, Taufiqur Rahman; Qadri, Firdausi; Lundgren, Anna (Frontiers in Immunology, 2021)
Enhancement of mucosal immune responses in children and infants using novel adjuvants such as double mutant heat labile toxin (dmLT) is an important goal in the enteric vaccine field. dmLT has been shown to enhance mucosal IgA responses to the oral inactivated enterotoxigenic Escherichia coli (ETEC) vaccine ETVAX. dmLT can enhance IL-17A production from adult T cells, which may increase the production and secretion of mucosal IgA antibodies. However, the adjuvant mechanism remains to be fully elucidated and might differ between infants and adults due to age-related differences in the development of the immune system. The main objective of this study was to determine how dmLT influences antigen presenting cells and T cells from infants compared to adults, and the role of IL-1β for mediating the adjuvant activity. Peripheral blood mononuclear cells (PBMCs) from Bangladeshi infants (6-11 months) and adults (18-40 years) were stimulated with the mitogen phytohaemagglutinin (PHA), the superantigen Staphylococcal enterotoxin B (SEB), ETVAX whole cell component (WCC) or E. coli lipopolysaccharide (LPS) ± dmLT, and cytokine production was measured using ELISA and electrochemiluminescence assays. The adjuvant dmLT significantly enhanced SEB- and PHA-induced IL-17A, but not IFN-γ responses, in PBMCs from both infants and adults. Blocking experiments using an IL-1 receptor antagonist demonstrated the importance of IL-1 signaling for the adjuvant effect. dmLT, ETVAX WCC and LPS induced dose-dependent IL-1β responses of comparable magnitudes in infant and adult cells. Depletion experiments suggested that IL-1β was mainly produced by monocytes. dmLT enhanced IL-1β responses to low doses of WCC and LPS, and the adjuvant effect appeared over a wider dose-range of WCC in infants. dmLT and WCC also induced IL-6, IL-23 and IL-12p70 production in both age groups and dmLT tended to particularly enhance IL-23 responses to WCC. Our results show that dmLT can induce IL-1β as well as other cytokines, which in turn may enhance IL-17A and potentially modulate other immunological responses in both infants and adults. Thus, dmLT may have an important function in promoting immune responses to the ETVAX vaccine, as well as other whole cell- or LPS-based vaccines in infants in low- and middle-income countries.